Sejarah Bahasa Indonesia: Bahasa Indonesia - Siti Nurohmah; Tridays Repelita (Jurnal Sekolah Dasar, 2025)
This research aims to analyze the development of the Indonesian language from the prehistoric era to the modern era. Using historical and comparative linguistic methods, this research traces the origins of the Malayo-Polynesian language as the forerunner of Indonesian, as well as the influence of Sanskrit, Arabic, Portuguese, Dutch and English on the development of its lexicon and grammatical structure. This study also examines the role of language policy during the colonial and post-independence periods in the formation of national identity and standardization of the Indonesian language. The research results show that Indonesian is a product of complex socio-political dynamics, reflecting a continuous process of assimilation and cultural adaptation. These findings enrich understanding of the evolution of the Indonesian language and highlight the importance of language policy in influencing the direction of its development. Keywords: Indonesian language, language history, historical linguistics, language policy, lexicon development.